A facile route to develop hydrophilicity on the polyolefin surface for biomedical applications. Issue 5 (12th January 2017) - Siddiqa, Akhtar J.; Maji, Somnath; Chaudhury, Koel; Adhikari, Basudam
Abstract: In this study, the surface of low‐density polyethylene (LDPE) was functionalized with maleic anhydride (MA) using solution grafting method in the presence of benzoyl peroxide (BPO), an initiator. The surface chemistry of the grafted LDPE was characterized using different characterization tools. The effect of MA grafting for analysis of bulk properties such as the change in mechanical strength and thermal properties was studied. Further, the nanoindentation study was performed to analyze the surface mechanical property after MA grafting. Biocompatibility studies were carried out using NIH‐3T3 cells through MTT assay test. FTIR analysis revealed the presence of carboxylic groups on LDPE surface. The contact angle value was found to be 44 ± 3°, which confirms the development of hydrophilicity in LDPE. Cell viability was found >75% in MTT assay. These results suggested that the prepared hydrophilic LDPE is a potential candidate for biomedical applications and surface coatings with other polar polymer.